HUBUNGAN PENDEKATAN KONTEKSTUAL BERBENTUK MEDIA GAMBAR DENGAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD INPRES 12 KABUPATEN SORONG - Troce Malaum; Syams Kusumaninggrum; Gika Apia (CV. Adiba Aisha Amira, 2025)
This study aims to determine whether or not there is a Relationship between Contextual Approach in the Form of Image Media and Students' Interest in Learning in the Science Subject of fourth Grade Students in SD Inpres 12 sorong regency. The method used in this study is a quantitative approach with a field study type. Data collection techniques use questionnaires and observation sheets for assessing interest in image media. From the accumulation of calculations with SPSS, it is known that the Sig. (2-tailed) values ​​are 0.000 <0.005 in pair 2 (experimental class), so Ho is rejected and Ha is accepted. So it can be concluded that there is a difference in the average between the pretest and posttest learning outcomes, which means that there is an influence of the use of image media in science learning. Based on the results of the study and discussion, it can be concluded that there is a relationship between the use of image media and students' interest in science learning in grade IV SD Inpres 12 Sorong Regency.. The calculation of the correlation coefficient r count was 0.922, sig. (2-tailed) of 0.000. Because the significance level that has been set is 0.000 <0.05 and r count is 0.922 for a significance level of 5% with df = 50 - 1 = 49, r table (0.666) was obtained, while the significance level of 10% with df = 50 - 1 = 49, r table (0.798) was obtained. After that, the r² regression test was 0.80, which means that it has a large effect of 85% on students' learning interest. This means that between the use of image media and learning interest in science learning in grade IV of SD Inpres 12 Sorong Regency, there is a very strong or very high correlation.